‘A republic, if you can keep it’ – separation of powers and its influence in American politics and jurisprudence - Vihmakoski, Frans (My University, 2024)
This Bachelor’s thesis covers the evolving jurisprudence of the United States Supreme Court’s current composition in order to highlight the recent changes in its separation of powers jurisprudence. The paper gives a background of how the understanding of the separation of powers and the Supreme Court cases governing it have evolved in the 20th and 21st centuries. The main research materials include legal literature and a wide range of Supreme Court cases. Each branch of government will be given a separate in-depth analysis about the cases that have influenced each branch and the implications that those cases have had for the checks and balances. The conclusion reached is meant to shed light on the Court’s actions from the perspective that they are meant to protect the Framers' vision of a government that is kept in check by ‘we the people’ and the system of checks and balances. The reader should come to understand that what matters the most in the Court’s deliberations is not how issues like abortion, the environment and gun control are ruled on, but how those decisions uphold the United States’ unique form of government.
Keywords: separation of powers, checks and balances, the Constitution, the United States Supreme Court